4-[(9-Ethyl-9H-carbazol-3-yl)methylideneamino]-1,5-dimethyl-2-phenyl-1 H-pyrazol-3(2H)-one - Asiri, A.M.; Khan, S.A.; Tan, K.W.; Ng, S.W. (International Union of Crystallography, 2010)
The imino-carbon double bond in the title Schiff base, C(26)H(24)N(4)O, has an E configuration. The 13-membered carbazolyl fused-ring (r.m.s. deviation = 0.056 angstrom) is nearly coplanar with five-membered pyrazole ring (r.m.s. deviation = 0.036 angstrom) [dihedral angle between the two systems = 10.4 (1)degrees]; the phenyl substituent is twisted by 51.1 (1)degrees with respect to the five-membered ring.